Preparation of Polyamide 6/CeO2 Composite Nanofibers through Electrospinning for Biomedical Applications - Xinyu Zhang; Xinggang Chen (International Journal of Polymer Science)
Polyamide 6 (PA6)/CeO2 composite nanofibers were prepared by electrospinning technique. The morphological, structural, and mechanical properties of the PA6/CeO2 nanofibers were investigated by using SEM, XRD, Fourier transform-infrared (FT-IR) spectroscopy, and an electronic universal tensile testing machine. SEM images revealed that the nanofibers were well oriented and had good incorporation with CeO2, the average diameter of composite fibers first decreases and then increases with the loading of CeO2. The crystallinity of fibers decreases after the addition of CeO2. The tensile strength of the fibers first increases and then decreases with the increasing concentration of CeO2. The proliferation properties of mouse macrophages and osteoblasts on the PA6/CeO2 nanofibers were analyzed by an in vitro cell compatibility test, the results show that PA6/CeO2 composite fibers is nontoxic to macrophages and osteoblasts and has good biocompatibility.